A Gold(I)‐Catalyzed Tandem Cyclization to Benzo[b]indeno[1, 2‐e][1, 4]diazepines from o‐Phenylenediamines and Ynones. Issue 18 (4th August 2020) - Xie, Fukai; Zhang, Bo; Chen, Yanyu; Jia, Hongwei; Sun, Lei; Zhuang, Kaitong; Yin, Lili; Cheng, Maosheng; Lin, Bin; Liu, Yongxiang
Abstract: A gold‐catalyzed tandem cyclization of o ‐phenylenediamines with ynones to synthesize benzo[ b ]indeno[1, 2‐ e ][1, 4]diazepine has been developed. The mechanism was explored by control experiments. The method provides a way to access a range of benzo[ b ]indeno[1, 2‐ e ][1, 4]diazepine derivatives in diversity‐oriented synthesis aiming at discovering structurally diverse scaffolds. Abstract :